2008
DOI: 10.1002/ajmg.a.32188
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of 13q associated with polymicrogyria

Abstract: Interstitial deletion of the long arm of chromosome 13 is a rare condition characterized by multiple clinical findings. We report a male dizygotic twin with an interstitial deletion of 13q and failure to thrive, hypotonia, polymicrogyria, bilateral foci of retinoblastoma, hearing loss, bilateral inguinal hernias, submucous cleft palate, and dysmorphic features including a triangular shaped face, broad forehead, small chin, prominent eyes, downslanting palpebral fissures, and a downturned mouth. Chromosome anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
14
2
Order By: Relevance
“…Both cases indicate that imbalances in 13q21 belong to the growing list of euchromatic polymorphisms, e.g., euchromatic variants that have no phenotypic effect. The only clinical observation in our patient is the history of recurrent abortions/ infertility thus our case does not support the theory of Kogan et al [2008] who hypothesized that haploinsufficiency of procadherin genes in 13q21 is associated with polymicrogyria and other malformations. However, with limited knowledge about the functional haploinsufficiency of the genes affected in our case, an association between the deletion and reproductive impairment cannot be excluded.…”
Section: Discussioncontrasting
confidence: 75%
“…Both cases indicate that imbalances in 13q21 belong to the growing list of euchromatic polymorphisms, e.g., euchromatic variants that have no phenotypic effect. The only clinical observation in our patient is the history of recurrent abortions/ infertility thus our case does not support the theory of Kogan et al [2008] who hypothesized that haploinsufficiency of procadherin genes in 13q21 is associated with polymicrogyria and other malformations. However, with limited knowledge about the functional haploinsufficiency of the genes affected in our case, an association between the deletion and reproductive impairment cannot be excluded.…”
Section: Discussioncontrasting
confidence: 75%
“…To date, only five patients with an interstitial 13q deletion involving the region 13q14.2 defined by array-based analyses have been reported. [13][14][15] Caselli et al 14 reported on one patient with normal clinical features and a small 1.7-Mb deletion, and two other patients with larger deletions of 19-45 Mb who showed variable clinical features including craniofacial dysmorphism, psychomotor delay, hypotonia, short stature and anomalies of feet and brain. A correlation of the extent of the deletion to the facial phenotype and other clinical features in patients with an interstitial 13q deletion proximal to the region 13q32 (group 1 of Brown's classification) is still wanting.…”
Section: Introductionmentioning
confidence: 99%
“…com. ] common feature of individuals with 13q deletions [Brown et al, 1993[Brown et al, , 1995Ballarati et al, 2007;Kogan et al, 2008], Kirchhoff et al [2009] determined that the smallest overlapping region in patients with microcephaly was the terminal region of chromosome 13q, approximately 6 Mb, between 13q33.3 (108 Mb) and 13q34, where more than 30 genes have been mapped. Indeed, in previous publication Walczak-Sztulpa et al [2008] suggested that a possible candidate gene for microcephaly could be located in this region.…”
Section: To the Editormentioning
confidence: 99%